Innovative practice of Non-Governmental Organisations (NGOs) working with out-of-school, unemployed youth in Cape Town : an exploratory study - Mutongwizo, Nyasha (Department of Social Development, 2016)
The following study is an exploration of the innovative practice of Non-Governmental Organisations (NGOs) that work with out-of-school, unemployed youth between the ages of 15 and 24 years in Cape Town. The current study meets three research objectives: describing the key characteristics of innovative practice; exploring the nature of NGO's engagement with out-of-school, unemployed youth (15-24 years) in Cape Town; and investigating the factors that promote or constrain innovative practice in these youth NGOs. The first objective of the current study is met through a literature review. Key characteristics of innovative practice are reviewed and the views of NGOs as innovators, as well as the voices of the skeptics of this view, are presented. Two key organisational conditions of 'learning' and 'organic' organisations are presented as being optimum for innovative practice. The literature review also explores the issue of youth unemployment from a global to a South African context; policies and strategies that the South African government has put in place to promote skills development, training and employment creation; the promotion of small business development as a viable employment strategy; and the role of NGOs in youth development. A survey among ten NGOs fulfils the second and third objectives of the current study. The survey's findings revealed that all the participating organisations considered their programmes to be innovative and to be providing both immediate and long-term benefits to their programme participants. It was one of the researcher's main findings that while these respondents claimed that their programmes were innovative and unique, some similarities could be found between them. The main obstacles to innovative practice were found to be funding constraints and the lack of human resource capacity. Despite these challenges, most respondents felt that the NGO sector was more innovative in comparison with both the government of South Africa and the private sector. Based on the findings, recommendations are offered to government, NGOs working with unemployed youth and research bodies. Recommendations for the networking of youth NGOs (for improved service delivery) and a recommendation on further research into the area of out-of-school, unemployed youth (to facilitate appropriate interventions) were found to be fitting. Includes bibliographical references (pages 89-95).